Characterization of protein kinase D PKD in the regulation of Drosophila melanogaster homeostasis - Khan, Zaid (2016)
Insulin signaling is one of the master keys for performing proper regulation of energy metabolism. Serious diseases such as cardiovascular disease, type 2 diabetes and obesity occur due to mis-regulation of insulin pathway. Therefore, it is necessary to recognize the factors that function in the production of insulin and it’s signaling. Drosophila melanogaster is the model organism used for this study in order to explore the function of Protein kinase D (PKD), which is a serine-threonine kinase. D. melanogaster has shown lower lipid content when PKD expression is reduced. The knockdown of PKD on transcription level in the D. melanogaster flies did not affect the transcription levels of both the insulin-like peptides (ILPs) and Adipokinetic hormone Akh. Starvation has affected the expression of different Ilps in the fly brain and high protein rich diets have affected the expression of PKD and Ilp3 in the fly brain.